Outdoor School Modeling at LPK Kaizen Nirel Center During the Covid-19 Pandemic Disaster - Purba, Ridhoi; Nauly, Meutia; Zaid (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 disaster has impacted the learning process, not only for normal children but also for children with special needs. They have the same right to get a quality education. This community service is addressed as an outdoor learning model and applies health protocol at LPK Kaizen Wireless Center (KNC). KNC is an institution that provides education and training services to children with special needs. The method used is consultation, and support for learning facilities following health protocols. This service is located at the location of KNC. The results of the service made KNC as an outdoor model learning and implementing health protocols were felt to be useful (perceived usefulness) such as being safe, comfortable, and providing optimal therapeutic stimulation during a pandemic; and felt easier to use (perceived ease-of-use), such as being effective and efficient in carrying out activities that do not have to be in outside areas. In the future, this service program can continue to empower the resources of teachers and therapists as well as parents, especially mothers of children with special needs to be able to support the growth and development of their children to become independent people in the future.